Germination of Sorghum CuItivars at Different pH Levels and Moisture Potentials - Bishnoi, U R; Garton, Stephen; Maiga, Alassane (Annals of Arid Zone, 2016)
Inadequate germination and field stand establishment causing low yield or crop failure in grain sorghum (Sorghum bicolor L. Moench) is common in arid and semi-arid tropical regions having erratic rainfall and variation in soil pH. Therefore, effects of water potential and soil pH on gennination of newly introduced U.S. grain sorghum cultivars in comparison to regional cultivars of West Africa were studied. Physiological germination (radicle emergence) of six American (SC283, SC574, SC689, B68181, SC33 and RTam 428) and four West African (Csm63, IS6705c, IS7173c and 7419c) sorghum cultivars was conducted at three osmotic potentials (control, -0.4 and -0.8 MPa) and at five points on tile pH scale (5.0, 6.0, 7.0, 8.0 and 9.0) in the laboratory. Genllination was decreased by 25% and 60% With decreased water potentials of -0.4 and -0.8 MPa, respectively, compared to controls. Alteration of pH from 7.0 significantly reduced germination in some cultivars. The effects on germination due to moisture and pH stress varied among cultivars. Cultivars SC283 and SC689 were most tolerant of, and sensitive to, low water potentials. Cultivar Csm63 was the most sensitive to low pH while B68181 showed similar response to high pH.